Choroidal thickness evaluation of healthy eyes, central serous chorioretinopathy, and fellow eyes using spectral domain optical coherence tomography in Indian population - Arora, Supriya (Indian J Ophthalmol, 2016)
AIM: The purpose of this study is to establish a normative database of subfoveal choroidal thickness (CT) in healthy young Indians using spectral domain optical coherence tomography (SD OCT). Evaluation and comparison of CT of central serous chorioretinopathy (CSC) and fellow eyes were also performed. MATERIALS AND METHODS: This was a prospective, cross-sectional, and observational study. It included 112 normal eyes of 112 healthy volunteers who had no evidence of ocular or systemic disease, 84 CSC eyes with acute, treatment-naïve CSC, and 69 fellow eyes with no evidence of neurosensory detachment or pigment epithelium detachment on SD OCT. Complete history, examination, and SD OCT were performed in all eyes. RESULTS: The mean age of 81 patients (84 eyes) with CSC was 35.04 ± 8.86 years, 69 fellow eyes was 34.61 ± 8.71 years, and 112 healthy volunteers (112 eyes) was 33.16 ± 9.4 years (P < 0.05). The mean subfoveal CT of CSC eyes was 429 ± 74.18 μ, fellow eyes was 360 ± 57.99 μ, and normal eyes was 301.80 ± 46.59 μ (P < 0.001). CONCLUSION: CT varies not only with age, axial length, and refractive error but also with races. Therefore, it is important to establish a normative database in a particular population before carrying out further research in diseased states. CT in CSC eyes is significantly thicker than fellow eyes, and CT of fellow eyes is significantly thicker than normal eyes. This reinforces the fact that choroidal permeability is increased in both eyes of patients with CSC.